Courses
Courses for Kids
Free study material
Offline Centres
More
Store

# Find the equation of tangent and normal to the curve ${\text{3}}{{\text{x}}^{\text{3}}}{\text{ - 4x + 7}}$ at the point whose abscissa is $1$.

Last updated date: 19th Jun 2024
Total views: 413.7k
Views today: 10.13k
Verified
413.7k+ views
Hint: As per the given information in the question, abscissa means x- axis’s point so x ${\text{ = 1}}$. We can calculate the slope of the curve using $\dfrac{{{\text{dy}}}}{{{\text{dx}}}}$ method. And also remember the information that tangent and normal are perpendicular to each other. And finally, we need to write the equation of the line using point-slope form.

Complete step by step solution: Given curve ${\text{3}}{{\text{x}}^{\text{3}}}{\text{ - 4x + 7}}$,
First of all calculating the coordinates of the point that can be given as ,
${\text{x = 1,}} \\ {\text{y = 3}}{{\text{x}}^{\text{3}}}{\text{ - 4x + 7}} \\ {\text{ = 3 - 4 + 7}} \\ {\text{ = 6}} \\ {\text{(x,y) = (1,6)}} \\$
Now, calculating the slope of tangent to the given curve at the designated coordinate,
${{\text{(}}\dfrac{{{\text{dy}}}}{{{\text{dx}}}}{\text{)}}_{{\text{x = 1}}}}{\text{ = (9}}{{\text{x}}^{\text{2}}}{\text{ - 4}}{{\text{)}}_{{\text{x = 1}}}} \\ {\text{ = 9(1) - 4}} \\ {\text{m = 5}} \\$
Hence as we know the slope and point so we can write the equation of line as ,
${\text{y - }}{{\text{y}}_{\text{1}}}{\text{ = m(x - }}{{\text{x}}_{\text{1}}}{\text{)}} \\ \Rightarrow {\text{y - 6 = 5(x - 1)}} \\ \Rightarrow {\text{y - 6 = 5x - 5}} \\ \Rightarrow {\text{5x - y + 1 = 0}} \\$
Above is the equation of tangent and now using the perpendicular condition to calculate the slope of normal’s line.
${{\text{m}}_1}{m_2} = - 1 \\ {\text{as, }}{m_1} = 5 \\ \Rightarrow {m_2} = \dfrac{{ - 1}}{5} \\$
Now, again using point slope method to write the equation of normal,
${\text{y - }}{{\text{y}}_{\text{1}}}{\text{ = m(x - }}{{\text{x}}_{\text{1}}}{\text{)}} \\ \Rightarrow {\text{y - 6 = }}\dfrac{{ - 1}}{5}{\text{(x - 1)}} \\ \Rightarrow {\text{5y - 30 = - x + 1}} \\ \Rightarrow {\text{5y + x = 31 = 0}} \\$

Hence , ${\text{5y - 30 = - x + 1}}$ is equation of normal.

Note: In common usage, the abscissa refers to the horizontal (x) axis and the ordinate refers to the vertical (y) axis of a standard two-dimensional graph.
A tangent to a curve is a line that touches the curve at one point and has the same slope as the curve at that point. A normal to a curve is a line perpendicular to a tangent to the curve.